Structural change in Ethiopia: is the country catching up or lagging behind? - Asmare, Fissha; Aman, Denekew; Ayalew, Tewodros; Ayenew, Workineh (Advances in Social Sciences Research Journal, 2017)
Attaining a sustained economic growth is the prime objective of any nation in the entire world. Some countries potentially tackle this challenge and can register an extensive economic progress. However, this is true for some developed countries only. In many developing countries achieving a persistent economic growth is a big challenge. Similarly, Ethiopia has been struggling for alleviating different macroeconomic instabilities. The country is suffering from the problem of food security, income inequality and BOP deficit. But recently the country has launched a new approach to economic growth, the growth and transformation plan (GTP). Primarily, this plan is envisaged to transform the country in the class of lower middle income countries with zero level of carbon emission in 2025. However, still the country is still challenged by different macroeconomic maladjustments. Inflation and significant level of unemployment are currently characterizing the country’s economy. But, some reports of still the country’s government stated that the country is going on the correct path of development. This calls an investigation on the nature of structural change in the country. Therefore, this study tries to explore structural change in the economy. It is also aimed on identifying in which sector the country achieves structural change. By using the kaldor verdon coefficient, shift share analysis, and Thrwill’s law as a measure of structural change, this study revealed that, the country has show a structural change in its economic progress. Indeed, the study also indicates that, within the period between 1990 and 2013 the country is notably not far from the world economy and it is in the process of catching up. The estimated coefficient of Kaldor- Verdroon for Ethiopian economy from 2005 to 2013 is greater than 0.5, therefore the country’s manufacturing sector is operating in the dynamic economies of scale and the country have a potential of catching up in the future. Key words: Structural change, kaldor- verdroon coefficient, GTP, Thrwill’s law